Analisis Tingkat Pelayanan Persimpangan dengan Metode MKJI 1997 (Studi Kasus : Simpang Jalan Lintas Timur Pangkalan Kasai – Batang Cenaku ) - Inanti Bathinuriani; Bobby Mauliantino; Nafriandi Nafriandi (Jurnal Sipil Terapan, 2023)
A crossroads is a meeting or crossing location of two or more roads and is a place where traffic conflicts occur. The East Crossroads Intersection of Pangkalan Kasai – Batang Cenaku is busy traffic lane because it is a connecting road between Seberida District –East Cross highway with Batang District My breath. The purpose of this research is to find the value of capacity, degree saturation, delay, queue opportunity to determine the level category services of the East Cross Road Intersection of Pangkalan Kasai - Batang Cenaku, and look for handling solutions from the results of service level intersections forlocation of the East Cross Road Intersection of Pangkalan Kasai – Batang Cenaku if traffic flow is hampered by using the 1997 MKJI method. Survey conducted for three days from 06.00 – 18.00 WIB. Based on the results survey and data analysis obtained the highest number of traffic on Sunday at 17.00 – 18.00 WIB at 818.7 pcu/hour, capacity (C) of 2156.24 pcu/hour, degree of saturation (DS) of 0.38, delay of 8.1026 sec/pcu, and the probability of queuing (QPatas – QPbottom) is 17.6480 – 6.9774%. From the results of the degree of saturation are known to be the level of service at the Crossroads East Cross Base Kasai - Batang Cenaku is B where the current is stable, but the starting speed is limited due to traffic conditions, the driver has enough speed to choose speed.